Unusual presentation of paediatric anaplastic large cell lymphoma (Bangladesh Journal of Medical Science, 2010)
Anaplastic large cell lymphoma (ALCL) is a rare disease. Among childhood non-Hodgkin lymphoma, it constitutes less than 20% of the incidence of all cases. The clinical presentation though is known to be much diversified, most of the patients will present with an enlarged palpable cervical lymphadenopaty. Other reported features include fever of unknown origin, nonspecific pain, cough, shortness of breath, fatigue and malaise. We report a case of ALK-positive ALCL in a patient who presented with submandibular abscess. After defaulted treatment, the mass became fungating externally with everted edge that mimic squamous cell carcinoma. Keywords: ALCL; pediatric; clinical presentation DOI: 10.3329/bjms.v8i4.4711 Bangladesh Journal of Medical Sciences Vol.8(4); October 2009 pp135-138